Online Shopping : How Customers See It - Agarwal, Varsha (International Journal For Multidisciplinary Research, 2022)
This study aims to understand how consumers are impacted by various aspects in the context of electronic commerce (e-commerce), as well as how e-satisfaction and e-loyalty are related. As the Internet has developed into a platform for online transactions, businesses now need to understand how customers see online shopping. This study began with the integration of pertinent literature before examining the factors that influence consumers' decisions to make purchases online. This study follows a consumer's behaviour and attitude towards online shopping. This study also examines a customer’s point of view and how a customer feels towards online shopping. This study revolves around the basic idea and concept of online shopping and its impact on a consumer and how a consumer starts to differentiate between online and offline shopping.
ISME
Keywords: E-commerce; Online Transactions; Online Shopping; Consumer’s Behaviour